Media społecznościowe jako narzędzie budowania relacji z klientem przez mikro- i małe przedsiębiorstwa - Agnieszka Chwiałkowska (Studia i Materiały)
The article presents the results of the research related to the use of social media by micro and small enterprises offering products for infants. The research focus included the activities on social media undertaken by these companies and the role social media play in their activities and development. Moreover, the awareness of the companies of the idea of social media was investigated. The research proves that social media constitute a very important communica- tion channel used by companies to build relationships with their customers. Social media are much more important here than traditiona; media. SMEs take advantage of the possibilities of low-cost possibilities to reach their customers as effective as bigger companies.